Direct and indirect effects of oil shocks on the price of selected agricultural products in oil exporting and importing countries - Abdolrasoul Ghasemi; saeed Kayghobadi sani (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2019)
In this paper, the Panel SVAR model has been utilized on monthly data (2006-2018) to study and compare the direct and indirect effects of oil shocks on real price changes of selected agricultural products in oil exporting and importing countries. The results show that oil shocks, besides direct effect, indirectly affect the prices through aggregate demand, currency and monetary shocks. The response of selected products to different types of shocks in two panels, depends on their degree of substitution to fossil fuels. As the soybeans and to some extent corn price changes, which are most used in the production of biofuels, vary by direction and pattern in two panels, while the price dynamics of wheat is similar. The share of currency shocks and interest rates in explaining price changes in importing countries is higher than the exporting countries, which the main cause can be traced to the more developed financial markets in importing ones. Also, the difference in price response to idiosyncratic and common currency shock in two panels indicates the necessity to study the behavior of each panel member separately. Therefore, a separate model for Iranian economy was also estimated for the purpose of more precise conclusions and policy proposals.